Saya bukan menteri : memoir wartawan negara - Zainudin Maidin, Tan Sri, 1938- (Sintok : Penerbit Universiti Utara Malaysia, 2016)
Anecdotes of author's as a journalist of politics and government in Malaysia.
Keywords: Zainuddin Maidin, -- Tan Sri, -- 1938-, -- Anecdots; Journalism -- Malaysia; Malaysia -- Politics and government -- Anecdotes